2017
DOI: 10.3892/mmr.2017.6179
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-185 regulates transforming growth factor-β1 and collagen-1 in hypertrophic scar fibroblasts

Abstract: Transforming growth factor-β1 (TGF-β1) and collagen type I (Col-1) serve a critical role in the development and progression of hypertrophic scarring (HS). The present study hypothesized that a post-translational mechanism of microRNAs (miR) regulated the expression of TGF-β1 and Col-1 in HS fibroblasts (HSFBs). A collection of 20 HS tissues was compared with corresponding normal tissues from clinical patients, and the expression of miR-185 was measured. Using PicTar, TargetScan and miRBase databases, it was id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 29 publications
0
26
0
Order By: Relevance
“…In addition, miR-203 targets the EMT-and cell invasion-promoting transcription factor Snail2 (Slug) (34) and SMAD3 (33,34) to prevent fibrosis. Furthermore, among the key downregulated miRNAs, miR-185 targets TGF-␤ and collagen type I to control tissue fibrosis (6,35) and miR-221 targets fibrosis-promoting osteopontin, which is also the target of the polyphenol epigallocatechin-3-gallate (EGCG), which is found in green tea and upregulates miR-221 (36). On the other hand, miR-9 is a key fibrogenic and oncogenic miRNA that targets E-cadherin and the tumor suppressor and transcription SRY-box 7 (SOX7) of the SOX transcription factor family (8,37).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, miR-203 targets the EMT-and cell invasion-promoting transcription factor Snail2 (Slug) (34) and SMAD3 (33,34) to prevent fibrosis. Furthermore, among the key downregulated miRNAs, miR-185 targets TGF-␤ and collagen type I to control tissue fibrosis (6,35) and miR-221 targets fibrosis-promoting osteopontin, which is also the target of the polyphenol epigallocatechin-3-gallate (EGCG), which is found in green tea and upregulates miR-221 (36). On the other hand, miR-9 is a key fibrogenic and oncogenic miRNA that targets E-cadherin and the tumor suppressor and transcription SRY-box 7 (SOX7) of the SOX transcription factor family (8,37).…”
Section: Resultsmentioning
confidence: 99%
“…Beaumont et al (13) demonstrated that miR-19b expression was reduced in patients with aortic stenosis, which may be a potential biomarker of increased myocardial collagen. Xiao et al (15) observed that in hypertrophic scar fibroblasts, miR-185 regulated the concentration of transforming growth factor-β1 and collagen I. Notably, Jing and Jiang (14) reported that miR-93 regulated collagen loss by targeting stromelysin-1 (MMP3) in human nucleus pulposus cells.…”
Section: Introductionmentioning
confidence: 99%
“…Another miRNA downregulated in hypertrophic scars is miR-185. Following bioinformatics target prediction analysis, miR-185 could indeed downregulate expression of TGF-β and collagen I in fibroblasts, affecting cell proliferation and apoptosis [352]. The proteolytic modulation of collagen function is regulated my miRNAs miR-10a and miR-181c, which affect this process in hypertrophic scar fibroblasts by targeting PAI-1 and uPA and increasing MMP-1 levels [353].…”
Section: Microrna -Ecm Interactions In Wound Healingmentioning
confidence: 99%